Financial Health Analysis and Indications of Going Concern at PT Acset Indonusa TBK in 2025 - Amrulloh Ghofilin Priyanto; Hasbi Albatsyah; Muhammad Najib; Nicolas Leonil; Sigit Purwanto; Herayati Herayati (Nomico, 2026)
This study aims to evaluate the financial health and identify the potential for going concern at PT Acset Indonusa Tbk based on the audited consolidated financial statements for the 2024–2025 period. The analysis was conducted using financial ratios covering liquidity, solvency, and profitability, then supplemented with the Altman Z-Score and Springate S-Score financial distress prediction models. The results show that the company still faces significant financial pressure, characterized by equity deficiencies, large net losses, negative operating cash flow, and violations of loan covenants. The Altman Z-Score and Springate S-Score calculations also place the company in the distress category, indicating a high risk to business continuity. These findings align with management's disclosure of material uncertainty regarding the company's ability to continue as a going concern, despite financial support from the parent entity. This study confirms that an unmodified audit opinion accompanied by an emphasis of matter paragraph does not always reflect a healthy financial condition. Therefore, investors, creditors, and other users of financial statements need to conduct a thorough evaluation, including reviewing the notes to the financial statements and key financial indicators, before making economic decisions.